THE IMPORTANCE OF LITERARY NOVELS IN DEVELOPING STUDENTS’ READING SKILLS THROUGH NATIONAL CONTENT - Kamoljonova Dilfuza Kholdorovna (World Scientific Research Journal, 2025)
Abstract. In the article you will get acquainted with the role of fiction in the upbringing of children, the analysis of works in the spirit of Pand-admonition.